2004
DOI: 10.1177/146642400312400110
|View full text |Cite
|
Sign up to set email alerts
|

Physical activity and sedentary behaviours in youth: issues and controversies

Abstract: There is growing concern over the effects of sedentary lifestyles on the health of young people. Recent rapid increases in juvenile obesity have received a great deal of attention in the scientific and popular press and have been attributed partly to television viewing, computer games and other sedentary behaviours. These are thought to compete with physical activity. There is a 'moral panic' concerning the 'couch kids' culture in modern western society. Project STIL (Sedentary Teenagers and Inactive Lifestyle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
199
3
21

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(237 citation statements)
references
References 16 publications
14
199
3
21
Order By: Relevance
“…13,53 Several studies have reported that these two behaviors are independent for young people 54,55 and also for adults. 12,15,35,56,57 In addition, gender differences have been reported previously in the associations between LTPA and TV watching. In a study by Sugiyama et al, 53 it was found that women who reported more time watching TV spent less time in LTPA, whereas such a relationship was not found in men.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…13,53 Several studies have reported that these two behaviors are independent for young people 54,55 and also for adults. 12,15,35,56,57 In addition, gender differences have been reported previously in the associations between LTPA and TV watching. In a study by Sugiyama et al, 53 it was found that women who reported more time watching TV spent less time in LTPA, whereas such a relationship was not found in men.…”
Section: Discussionmentioning
confidence: 98%
“…11 In parallel with physical activity, sedentary behavior is of particular interest, as a complementary dimension related to specific health outcomes. 12,13 Sedentary behavior refers to occupations that do not increase energy expenditure substantially above the resting level and includes activities such as sleeping, sitting, lying down, watching television (TV) and other forms of screen-based entertainment. 14 Some studies have suggested that sedentary behavior, typically assessed by the time spent watching TV, is associated with increased obesity risk.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, leisure researchers have exercised caution in considering the basis of concern for processes they review in the context of moral panics. For example, the bases of moral panics in relation to 'football hooligans', 'couch kids', child abuse in sport, and young people at risk through binge drinking, have been questioned by Redhead (2007), Biddle et al (2004), Brackenridge (2001Brackenridge ( , 2002 3 , Hickey et al (2009), respectively. Valentine et al (2008, p. 28) are equally cautious, arguing that moral panics about binge drinking are 'implicitly producing a monolithic image of alcohol consumption in urban areas that fails to acknowledge the socio-spatially differentiated nature of practices of alcohol consumption and regulation'.…”
Section: Moral Panic Students and Leisurementioning
confidence: 99%
“…Sin embargo, se trata de una hipótesis controvertida, puesto que otros trabajos indican que el uso de medios tecnológicos y la actividad física son conductas que pueden coexistir (Biddle, Gorely, Marshall, Murdey y Cameron, 2003). Incluso otras investigaciones seña-lan que los niños y adolescentes más activos son los que dedican más tiempo a los videojuegos (Marshall, Biddle, Sallis, McKenzie y Conway, 2002;Martín, 2007).…”
Section: Introductionunclassified